Characterization of a-CNx Thin Films prepared by RF-PECVD Technique for humidity sensor - R. Awang,; N.F.H Aziz,; N. Purhanudin,; Z. Zalita, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this work, amorphous carbon nitride (a-CNx) thin films were deposited by radio frequency (RF) plasma enhanced chemical vapor deposition (RF-PECVD) technique. The RF power and gas mixture of methane (CH4) and nitrogen (N2) flow was kept constant, while the electrode distance was varied from 1 to 6 cm. The effect of electrode distance on the chemical bonding, morphology and humidity sensing responses of the films were investigated. Fourier transform infra-red spectroscopy (FTIR) studies showed a systematic change in the spectra and showed three main peaks namely the G and D-peak, C≡N triple bonds and C-H/O-H groups. Uniform and porous morphology was observed for films deposited at smallest distance followed by non-porous cubicle-like grain as electrode distance increased. Subsequently formation of vertically aligned nanostructures apparent both from its surface and cross section images by increasing of electrode distance to the fullest. The humidity sensing property has been studied by recording their resistance response to relative humidity (RH) at room temperature. It was found that the resistance value decreases from 15.4 to 3.6 kΩ with the increase in RH from 9 to 85%, with the highest sensitivity of 77% for film deposited at smallest distance of 1 cm.